2020
DOI: 10.3390/molecules25081764
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Loaded Halloysite Nanotubes as Mesocatalysts for Fischer–Tropsch Synthesis

Abstract: Halloysite aluminosilicate nanotubes loaded with ruthenium particles were used as reactors for Fischer–Tropsch synthesis. To load ruthenium inside clay, selective modification of the external surface with ethylenediaminetetraacetic acid, urea, or acetone azine was performed. Reduction of materials in a flow of hydrogen at 400 °C resulted in catalysts loaded with 2 wt.% of 3.5 nm Ru particles, densely packed inside the tubes. Catalysts were characterized by N2-adsorption, temperature-programmed desorption of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…S BET (m 2 g −1 ) S EXT (m 2 g −1 ) V micro (cm 3 g −1 ) V meso (cm 3 g −1 ) 2019b; Lo Dico et al, 2019;Lisuzzo et al, 2020a;Farinmade et al, 2020;Saleh et al, 2020;Stavitskaya et al, 2020). Moreover, this clay does not show toxic effects and it is biocompatible (Fakhrullin and Lvov, 2016;Rozhina et al, 2020;Rozhina et al, 2021).…”
Section: Sepiolite Samplesmentioning
confidence: 97%
“…S BET (m 2 g −1 ) S EXT (m 2 g −1 ) V micro (cm 3 g −1 ) V meso (cm 3 g −1 ) 2019b; Lo Dico et al, 2019;Lisuzzo et al, 2020a;Farinmade et al, 2020;Saleh et al, 2020;Stavitskaya et al, 2020). Moreover, this clay does not show toxic effects and it is biocompatible (Fakhrullin and Lvov, 2016;Rozhina et al, 2020;Rozhina et al, 2021).…”
Section: Sepiolite Samplesmentioning
confidence: 97%
“…[22] Compared with CNTs, the HNTs is cheaper, has more abundant reserves, is non-toxic and has good compatibility. In view of the above structural characteristics and lower economic costs, the HNTs have been widely used as composite fillers, [23][24] catalyst carriers, [25][26] environmentally friendly adsorbents, [27][28] micro-reactors, [29] and templates for synthesizing functional materials. [30][31][32] Studies have shown that aniline, pyridine, thiophene, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The outer surface of nanotubes consists of silica, while the inner surface is made of alumina [ 21 ]. Tubular structure with possibilities for modification combined with thermal and mechanical stability, low acidity of halloysite make it an interesting support for FTS catalysts [ 22 , 23 ]. As the most active catalysts are those with 8–9 nm Co nanoparticles [ 24 , 25 ], the mesoporous lumen of halloysite is a perfect place for Co nanoparticles with the favourable size.…”
Section: Introductionmentioning
confidence: 99%